A Mendelian randomization study to examine the causal associations of circulating micronutrient levels with frailty risk - Kuribanjiang, Kaidiriyan; Min, Yiping; Yan, Shikang; Chen, Simin; Aiheti, Nuerbiyamu; Wupuer, Abudunaibi; Wang, Jie; Peng, Xing; Li, Yihan; Li, Huilong; Dong, Yiran; Fan, Yuanlin; et al. (Frontiers in Nutrition, 2024)
Background: Observational studies have shown that micronutrients can affect the occurrence of frailty. However, it is not clear whether there is a causal relationship between the two. This study aimed to explore the causal relationship between circulating micronutrient levels and frailty risk using a two-sample Mendelian randomization (TSMR) approach.We gathered and screened instrumental variables (IVs) for six circulating micronutrients, including vitamin B12, vitamin B6, folate, vitamin C, vitamin D, and vitamin E, from published genome-wide association studies (GWAS) and the IEU OpenGWAS open database. Summary statistics for frailty were obtained from a GWAS meta-analysis, including the UK Biobank and TwinGene (N = 175,226). We performed two independent TSMR analyses and a meta-analysis based on the two independent MR estimates to assess the causal relationship between circulating micronutrientn and frailty.Results: Our study found, no causal relationship between genetically predicted vitamin D (β=-0.059, P=0.35), vitamin B6 (β=0.006, P=0.80), vitamin E (β=-0.011, P=0.79), vitamin C (β=-0.044, P=0.06), vitamin B12 (β=-0.027, P=0.37), and folate (β=0.029, P=0.17), with frailty. Conclusions: This study showed that these six micronutrients did not reduce the risk of developing frailty. However, we think it is necessary further to investigate the relationship and mechanisms between micronutrients and frailty using methods such as randomized controlled trials.